Education, social factors, and health beliefs in health and health care services - Kronenfeld, Jennie J. (Bingley, U.K. : Emerald, 2015)
This volume provides a unique sociological focus on education, social factors and health beliefs in health and health care, including a review of the literature to date. Beliefs and health beliefs are considered, including one study evaluating cross-national differences in public beliefs about the causes of health and the role of these beliefs in shaping attitudes to health policy. Another study focuses on the complexity and variation of health care system distrust across neighborhoods in one US city. The topic of education is addressed, including a focus on the importance of identification and intervention in low health literacy. Mental health issues are considered in the context of help-seeking, connections, transitions and utilization of care among adolescents. Social factors are reflected upon including race and ethnicity, literacy and socioeconomic status. Coverage also includes special and traditionally less visible populations, including the health of prisoners and carers of people with autism."
The politics of health beliefs: cross-national evidence / Jason Schnittker -- Psychological distress, nativity, and help-seeking among Filipiamericans / Ethel G. Nicdao, Aileen A. Duldulao, David T. Takeuchi -- Becoming an expert autism caregiver: health literacy and community catalysts / Cara A. Chiaraluce -- "It's not the doctor, it's me": how self-blame obscures language and other structural barriers to diabetes care among low-income Latinos with limited English proficiency / Claudia Chaufan, Hegla Fielding, Catherine Chesla, Alicia Fernandez -- Examining the complexity and variation of health care system distrust across neighborhoods: implications for preventive health care / Tse-Chuan Yang, I-Chien Chen, Aggie J. Noah -- Personal religiosity and mental health care utilization among adolescents / Thomas Christian Quinn, Rebecca L. Utz -- Connections and transitions in mental health care organizations and systems / Michael Polgar -- Support for HIV testing and HIV criminalization among offenders under community supervision / Brad Barber, Bronwen Lichtenstein -- Race and socioeconomic status: public perceptions toward quality and access to care in the Affordable Care Act / Neale R. Chumbler, Samir P. Desai, Justin B. Ingels, Kevin K. Dobbin -- Racial and ethnic differences in trust in sources of health information: a generalized distrust in physicians / Celeste Campos-Castillo -- A place to trust: black Protestant affiliation and trust in personal physicians / Abigail A. Sewell, Rashawn Ray -- Education, other social factors, and health beliefs and health care services / Jennie Jacobs Kronenfeld -- Identifying and mapping "hot spots" of low health literacy: a potential tool to guide intervention / Laurie T. Martin, Teague Ruder, José J. Escarce, Bonnie Ghosh-Dastidar, Daniel Sherman, Marc N. Elliott, Chloe E. Bird, Allen Fremont, Charles Gasper, Arthur Culbert, Nicole Lurie -- Education and self-awareness of health: toward a better understanding of self-rated health / Heeju Sohn.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Disease & Health Issues; General practice; Personal & public health; Health education; Social medicine